Innovation and leadership: A study of organizations based in the United Arab Emirates - Ruchi Agarwal; Babeet Gupta (Foundations of Management, 2021)
The successful practice of innovation in any organization demands the integration and interaction of individual, collective, and organizational climate levels of management. Leadership styles have an impact on all these three levels of management. However, little work has been done to assess this impact, especially in the context of United Arab Emirates (UAE)-based organizations. This study was conducted with the purpose of assessing whether leadership processes, tools, and techniques differ in innovative organizations and, thereafter, propose general leadership requirements for innovative projects in the UAE. This study adopts statistical data-processing methods, such as descriptive statistics, the reliability of the instrument, correlation, and regression analysis. Data obtained through a survey of UAE-based organizations were used for analyzing whether innovativeness (as perceived by employees) is statistically correlated with leadership dimensions. The research results show that the transformational leadership style scores better over transactional leadership when it comes to predicting innovations.
Keywords: M10; O31; O30; 650; leadership; leadership style; innovation processes; innovation culture